PENGGUNAAN MONOMER NAFION SEBAGAI PEMBAWA PROTON (H + ) DENGAN METODE TEORI FUNGSI KERAPATAN - Alhabib, Albar; Gunawan, Rahmat; Sitorus, Saibun (JURNAL KIMIA MULAWARMAN, 2014)
Research which has been conducted in this study aims to determine the use of the compound as a Nafion membrane in a Proton Exchange Membrane system (PEM) Fuel Cells which acts as a proton exchange (H + ). After assessment and computational chemistry calculations by calculating the value of energy optimization and molecular orbital energies obtained in the form of the HOMO and LUMO energy. Value calculation is done by using the calculation method of Density Function Theory (density function theory). The analysis showed Nafion energy value of -0.04358 x 10-18 J and Nafion after bringing energy protons (H+) of -0.07629 x 10-18 J. In this case proved that the PEM system of exchanging protons (H + ) is characterized by the presence of increased energy electron activity.Keywords : Proton Exchange Membrane, Fuel Cells, Nafion, Proton (H + ), the activity of electrons, density functional theory, the energy of the HOMO, LUMO energy.